2011
DOI: 10.1111/j.1475-6773.2011.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Doctor Responses to Changes in Incentives for Influenza Immunization under the U.K. Quality and Outcomes Framework Pay‐for‐Performance Scheme

Abstract: Objective. To analyze the effect of setting higher targets, in a primary care pay-forperformance scheme, on rates of influenza immunization and exception reporting. Study Setting. The U.K. Quality and Outcomes Framework links financial rewards for family practices to four separate influenza immunization rates for patients with coronary heart disease (CHD), chronic obstructive pulmonary disease, diabetes, and stroke. There is no additional payment for immunization rates above an upper threshold. Patients for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 18 publications
(19 reference statements)
3
65
0
1
Order By: Relevance
“…We identified seven cohort studies, one prospective 21 and six retrospective, [22][23][24][25][26][27] and one simulation study. 28 Three included studies 25,26,28 examined threshold changes in the QOF, and found that quality continued to increase after increases in maximum thresholds, with lower-performing providers improving significantly more than those who were performing at a high level under the previous threshold.…”
Section: Implementation Processes (8 Studies)mentioning
confidence: 99%
See 2 more Smart Citations
“…We identified seven cohort studies, one prospective 21 and six retrospective, [22][23][24][25][26][27] and one simulation study. 28 Three included studies 25,26,28 examined threshold changes in the QOF, and found that quality continued to increase after increases in maximum thresholds, with lower-performing providers improving significantly more than those who were performing at a high level under the previous threshold.…”
Section: Implementation Processes (8 Studies)mentioning
confidence: 99%
“…28 Three included studies 25,26,28 examined threshold changes in the QOF, and found that quality continued to increase after increases in maximum thresholds, with lower-performing providers improving significantly more than those who were performing at a high level under the previous threshold. 25,26 In addition, we identified three studies examining clinical process, and patient outcome incentives were removed from a measure. One study, of the QOF, found that the level of performance achieved prior to the incentive withdrawal was generally maintained, with some difference by indicator and disease condition.…”
Section: Implementation Processes (8 Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…160 This assumption was based on vaccination rates of 50% and between 80% and 93% reported in Spanish and UK studies. 161,162 The average number of days and cost of home oxygen therapy received in each severity group was derived from expert opinion reported in Hertel et al (2012). 140 Smoking-cessation advice and pulmonary rehabilitation are also recommended by NICE as usual care for COPD patients.…”
Section: Routine Health-care Visitsmentioning
confidence: 99%
“…Primary care physicians and pediatricians should be more actively involved and be given greater responsibilities in increasing vaccination coverage rates. Incentives to primary care physicians and pediatricians, when deemed strategic, 15 should be conditional to population-level coverage targets rather than to the number of vaccines administrated; 8. It is of fundamental importance to address the growing phenomenon of the 'vaccine hesitancy'.…”
mentioning
confidence: 99%